Effects of auricular acupoint pressing combined with modified Wendan decoction in the treatment of essential hypertension and accompanying insomnia (耳穴压豆联合加味温胆汤口服治疗原发性高血压伴失眠的效果观察) - ZHAO Liyun (赵丽云); LIU Qing (刘青); LI Yigen (李乙根); XU Wenwei (徐文伟) (中西医结合护理)
Objective To investigate the effect of auricular acupoint pressing combined with modified Wendan decoction in the treatment of essential hypertension and accompanying insomnia. Methods By adopting a convenient sampling method, totally 76 patients with primary hypertension and insomnia who were admitted to the Department of Traditional Chinese Medicine of Guangzhou Medical University Affiliated Hospital from January 2023 to August 2024 were included as research objects. These patients were randomly divided into two groups, with 38 patients in each group. In the control group, patients received conventional antihypertensive drug therapy and standard nursing care; In the observation group, in addition to receiving the same standard treatment as the control group, patients also received auricular acupoint pressing therapy and oral treatment with modified Wenpan decoction. The main objective of the study was to evaluate the changes in sleep quality (assessed using the Pittsburgh Sleep Quality Index), anxiety (assessed using the Hamilton Anxiety Scale), depression (assessed using the Hamilton Depression Scale), and blood pressure levels in the two groups before and after treatment. Results After treatment, the PSQI, HAMA, and HAMD scores in both groups were lower than those before treatment, and scores of observation group were significantly lower than those of the control group (P＜0. 05). After treatment, both groups had lower diastolic blood pressure and systolic blood pressure than those before treatment (P＜0. 05), and patients in the observation group had better outcomes in blood pressure reduction compared with those in the control group (P＜0. 05). Conclusion Auricular acupoint pressing combined with modified Wendan decoction is effective in lowering blood pressure, improving sleep quality and relieving anxiety and depression of patients with essential hypertension and accompanying insomnia. (目的 探讨耳穴压豆结合加味温胆汤口服治疗原发性高血压伴失眠症状患者的效果。方法 采用方便抽样的方法选取2023 年1月—2024年8月广州医科大学附属中医医院收治的76例原发性高血压伴失眠的患者为研究对象。采用随机数字表法将患者分为对照组和观察组, 各38例。对照组患者接受常规降压药物治疗和标准护理干预, 观察组在对照组基础上增加耳穴压豆联合加味温胆汤口服治疗。两组患者治疗观察周期均为10 d。采用匹兹堡睡眠质量指数(PSQI)评估患者睡眠质量, 采用汉密尔顿焦虑量表(HAMA)和汉密尔顿抑郁量表(HAMD)评估患者负性情绪, 记录患者血压水平变化。结果 治疗后, 两组PSQI、HAMA和HAMD量表评分均较治疗前降低, 且观察组评分低于对照组, 差异有统计学意义(P＜0. 05)。治疗后, 两组收缩压、舒张压水平较治疗前降低, 且观察组血压水平改善幅度优于对照组, 差异有统计学意义(P＜0. 05)。结论 耳穴压豆联合加味温胆汤口服治疗方式在降低血压、改善睡眠以及减轻焦虑和抑郁情绪方面显示出良好的效果。)